Temporal evolution of patterns and processes related to subsidence of the coastal area surrounding the Bevano River mouth (Northern Adriatic) – Italy. (May 2015) - Taramelli, A.; Di Matteo, L.; Ciavola, P.; Guadagnano, F.; Tolomei, C.
Abstract: Subsidence is a widespread phenomenon in the Emilia-Romagna, particularly important along the littoral because the coastal system consists of sandy beaches and coastal wetlands, particularly in the area of the Delta Po Plain. The coasts are affected by a marked natural subsidence, because of tectonic processes and recent sediments consolidation. Since the second half of the last century, the subsidence in coastal area has increased significantly due to intense human activity, namely gas extraction and groundwater exploitation. The work presented in this paper aimed at investigating the temporal evolution of patterns and processes on a stretch of coast located between Lido di Dante and Lido di Classe, including the mouth of the Bevano river near Ravenna (Italy), using remotely sensed datasets. An innovative integration of remote sensing and monitoring method (Permanent Scatter Interferometric Synthetic Aperture Radar – PSInSAR, Small BAeline Subset – SBAS and Empirical Orthogonal Function – EOF analysis of 20 years of Landsat) has been used to study the temporal evolution of subsidence and its correlation with natural and anthropogenic causes. Results show an increase of the subsidence rates obtained for the last decade: the amount of subsidence due only to natural causes is typically a few millimetres per year, while the man-induced subsidence reaches values of several millimetres per years. Marshlands reclamation, groundwater pumping for agricultural and industrial purposes and methane extraction from gas fields near the coastline are the principal anthropogenic causes. Subsidence in combination with sea level rise will get worse inundation risk from the rivers and widens the coastal areas affected by storm surges and tidal inundation. This makes subsidence an insidious threat having significant cumulative effects on flood risk or the integrity of water defenses and infrastructure. Highlights: Temporal evolution of patterns and processes on a stretch of coast. Multi-temporal analysis of processes and trends related to subsidence in coastal landscapes. Marshlands reclamation, groundwater pumping and methane extraction from gas fields are the main anthropogenic causes.